Islamic Law Review of the Principle of Freedom of Contract in Murabahah Contracts - Mardiaton, Mardiaton; Umar, Mukhsin Nyak; Hasnita, Nevi (Sahabat Publikasi, 2024)
In the banking world there is a tendency for standard contracts, in the form of contracts that have previously been determined and determined unilaterally in terms of the content and form of the contract with the intention of being addressed to the public with the same clauses, are continuous and are usually printed and detailed and cannot be negotiated. Likewise, what applies to Bank Aceh Syariah, the contents of the contract are deliberately left blank to give the customer the opportunity to negotiate and are filled in after an agreement is reached. This kind of contract limits the customer and does not provide a balanced position for either party, who basically has the same opportunity to determine what is desired in the contract. The application of the principles of al-hurriyah, fairness and balance between parties in contracts has been limited in banking. For this reason, this writing aims to find out how the process of making a murâbahah contract/agreement is, the position of the customer and the Aceh Syariah bank in formulating the murâbahah contract and the application of the principle of freedom of contract in the process of making the murâbahah contract according to a review of Islamic law at PT. Bank Aceh Syariah Sub-Branch of UIN Ar-Raniry Banda Aceh. This research is categorized as qualitative research based on data collection methods through Library Research and field research. Based on the studies that have been carried out, the results show that the process of making a murabahah contract/agreement at PT. Bank Aceh Syariah does not fully involve the customer, the customer only has the opportunity to read the contract which has been fully prepared by the bank, so that the position of the customer and the bank is not equal. The bank is in a stronger position and can unilaterally determine the contents of the contractual clauses agreed upon, while the customer is in a weak position and must accept all the contents of the clauses that have been determined by the bank. A position like this shows that the principles of freedom, justice and balance in contracts cannot be fully applied in the process of making murabahah contracts/agreements at PT. Bank Aceh Syariah Capem. UIN Ar-Raniry Banda Aceh.